2023
DOI: 10.3390/ijms24032142
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Protein O-GlcNAcylation in Liver Metabolism: Implications for Diabetes and NAFLD

Abstract: O-linked b-N-acetyl-glucosaminylation (O-GlcNAcylation) is one of the most common post-translational modifications of proteins, and is established by modifying the serine or threonine residues of nuclear, cytoplasmic, and mitochondrial proteins. O-GlcNAc signaling is considered a critical nutrient sensor, and affects numerous proteins involved in cellular metabolic processes. O-GlcNAcylation modulates protein functions in different patterns, including protein stabilization, enzymatic activity, transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 127 publications
0
2
0
Order By: Relevance
“…FXR activation enhances glycogen synthesis by promoting direct or indirect phosphorylation of glycogen synthase kinase‐3 beta, a pivotal modulator in glycogen synthase pathway 27 . It also governs gluconeogenesis via phosphoenolpyruvate carboxykinase and glucose‐6‐phosphatase 13 as well as inhibits glycolysis via carbohydrate response element‐binding protein 28 and glucagon‐like peptide 1 (GLP‐1) 29 . Additionally, FXR activation promotes β‐oxidation of fatty acids and regulate serum lipoprotein levels via peroxisome proliferator‐activated receptor alpha, 30 sterol regulatory element‐binding protein‐1c, 31 apolipoprotein A‐I, 32 apolipoprotein B, 33 and apolipoprotein C‐II/III, 32 resulting in a reduction in hepatic fat content.…”
Section: Effect Of Fxr Activation On Nafld/masldmentioning
confidence: 99%
“…FXR activation enhances glycogen synthesis by promoting direct or indirect phosphorylation of glycogen synthase kinase‐3 beta, a pivotal modulator in glycogen synthase pathway 27 . It also governs gluconeogenesis via phosphoenolpyruvate carboxykinase and glucose‐6‐phosphatase 13 as well as inhibits glycolysis via carbohydrate response element‐binding protein 28 and glucagon‐like peptide 1 (GLP‐1) 29 . Additionally, FXR activation promotes β‐oxidation of fatty acids and regulate serum lipoprotein levels via peroxisome proliferator‐activated receptor alpha, 30 sterol regulatory element‐binding protein‐1c, 31 apolipoprotein A‐I, 32 apolipoprotein B, 33 and apolipoprotein C‐II/III, 32 resulting in a reduction in hepatic fat content.…”
Section: Effect Of Fxr Activation On Nafld/masldmentioning
confidence: 99%
“…It is catalyzed by the O-GlcNAc transferase (OGT) and removed by the O-GlcNAcase (OGA). Decades of glycobiology research have witnessed emerging chemical and biological tools (3,4) that have demonstrated that O-GlcNAc occurs on about 5 000 proteins and regulates tumorigenesis and immunotherapy (5), ferroptosis (6), protein aggregation and phase separation (7), stem cell biology (8), liver metabolism (9), neurodevelopment and various stress response pathways (10).…”
Section: Introductionmentioning
confidence: 99%